Translation Difficulties Encountered by Yemeni EFL Learners in the Faculty of Education, Thamar University - Ahmed Kaid Thabet Alshokhada; Ameen Ali Mohammed Algamal (الآداب)
The present study aimed to investigate the linguistic, cultural, and curriculum-related translation difficulties encountered by Yemeni English as a foreign language (EFL, henceforth) learners in the Faculty of Education at Thamar University, Yemen.  The study sample comprised 41 participants. To collect the data, a questionnaire was administered as study instrument and the data were analysed via SPSS programme, version 20. The study employed the quantitative approach to provide a comprehensive understanding of the topic under study. The study made an attempt to identify the common translation difficulties, explore students' perceptions of their challenges, and analyze the underlying causes.  The findings revealed the significant difficulties related to grammatical differences between English and Arabic, vocabulary acquisition, cultural nuances, and the complexities of conveying meaning accurately and appropriately. The study offered pedagogical recommendations to improve translation instruction, aiming to equip learners with the necessary skills to succeed in translation-related fields.